2020
DOI: 10.3390/en13205454
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Integrated Design and Control of Electrified Vehicles

Abstract: From a control perspective, the energy management system and the thermal management system of an electrified vehicle are often developed separately, which may not yield the optimal solution. Moreover, an optimal system design requires concurrent plant (topology and size) and controller optimization, which should apply to both energy and thermal domains. This paper originally provides a comprehensive analysis of design and control optimization layers to reveal the interconnections between them and how they infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 78 publications
0
13
0
Order By: Relevance
“…Thermal management of electrified vehicles is widely discussed in the literature. Several review papers can be found addressing the problem of the thermal management for vehicle subsystems [4][5][6][7][8] with special reference to batteries [9][10][11][12][13][14][15][16][17][18][19][20][21][22], for the whole vehicle [23][24][25] or from a modeling perspective [26,27]. The present review aims to provide the designer of the thermal management system the most relevant information about the components, while focusing on the system.…”
Section: Introductionmentioning
confidence: 99%
“…Thermal management of electrified vehicles is widely discussed in the literature. Several review papers can be found addressing the problem of the thermal management for vehicle subsystems [4][5][6][7][8] with special reference to batteries [9][10][11][12][13][14][15][16][17][18][19][20][21][22], for the whole vehicle [23][24][25] or from a modeling perspective [26,27]. The present review aims to provide the designer of the thermal management system the most relevant information about the components, while focusing on the system.…”
Section: Introductionmentioning
confidence: 99%
“…This type of design problem can be tackled by different approaches. An overview of design and control optimization methodologies is given in [7,8]. As presented in [7], there are generally four approaches to solve the design (plant) and control (controller) problem.…”
Section: Introductionmentioning
confidence: 99%
“…An overview of design and control optimization methodologies is given in [7,8]. As presented in [7], there are generally four approaches to solve the design (plant) and control (controller) problem. With respect to solution optimality, simultaneous and nested coordination schemes outperform iterative and sequential ones, although depending on the coupling and how sensitive the solution is to uncertainties in the design parameters.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, CAVs can make real-time decisions by exploiting increased situational awareness gained from sensory data. While the main focus in the development of CAVs has been on driving safety and comfort, CAVs implications on energy consumption have also been considered, see [4][5][6][7] and the references therein. Most of the studies thus far have focused on reducing the traction power losses (e.g., eco-driving, platooning, cooperative adaptive cruise control).…”
Section: Introductionmentioning
confidence: 99%